POLITIK HUKUM ISLAM DALAM SISTEM HUKUM TATA NEGARA REPUBLIK ISLAM IRAN - Undang Hidayat (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2014)
Iran is one of the Muslim countries with predominantly population which follow the Shiite ideology and system of government as well as representing prototife modern Islam. Imamate system applied in the constitutional system of the Islamic Republic of Iran represents a form of legal awareness and political will of the authorities to submit to Islamic legal doctrines. The most unique characteristic of the political development of Islamic law in Iran is political reform in the early days after the Islamic revolution, Ayatollah Khumayni perform as well as religious and political leaders. But in its development, religious leaders separated by political leaders. However, the fact that khumayni still the religious leaders and the president in the political perspective. Thus, all policies in the various State agencies in Republic Islam of Iran must be following to Khumayni.